Allosteric activation mechanism of DriD, a WYL-domain containing transcription regulator - Emily Cannistraci; Bindu Y. Srinivasu; Jose Chavez Orozco; Kevin Gozzi; Thomas E. Wales; Maria A. Schumacher (Communications Biology)
Abstract WYL-domain containing transcription factors regulate fundamental processes in bacterial physiology, yet how these proteins sense cellular cues to elicit an allosteric response is not well understood. Here we describe the allosteric activation mechanism of DriD, a Caulobacter crescentus homodimeric WYL-domain containing transcription regulator that activates a non-canonical DNA damage pathway. DriD senses ssDNA, produced upon DNA damage via interaction with its WYL domain. This stimulates DriD target DNA binding. However, its DNA-binding domains (DNABDs) are 50 Å from the WYL-domains and linked by a three-helix bundle domain (3HB). Using a combination of crystallography, biochemistry, and HDX-MS we unveil an allosteric mechanism whereby an inhibitory interaction, formed between the DriD DNABD and 3HB in the apo form, is freed upon ssDNA binding, allowing target DNA binding. These findings may serve as a model for understanding activation by the large family of homodimeric WYL activators, including those in pathogenic bacteria.